Effect of Working Capital Effectiveness and Growth Opportunity on Profitability - Sari, Ratna (Advances in Economics & Financial Studies, 2023)
This study aimed to analyze the effect of cash turnover, accounts receivable turnover, inventory turnover and Growth Opportunity on Manufacturing Companies' Profitability on the Indonesia Stock Exchange. The type of data used in this study is quantitative data in the form of numbers in the form of financial reports on manufacturing companies listed on the Indonesia Stock Exchange in the period 2017 -2020 . Data sources in research are secondary data, namely in written form or company documents. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, classic assumption tests (normality test, heteroscedasticity test, multicollinearity test, autocorrelation test), and testing all hypotheses through the partial test (t test) and coefficient test determination. Based on hypothesis testing this study, it shows that the variable cash turnover, accounts receivable turnover, and inventory turnover positively and significantly affect profitability proxied by return on assets (ROA). In contrast, the growth opportunity variable has no significant effect on profitability proxied by return on assets (ROA)